Ethics of Socially Disruptive Technologies An Introduction - van de Poel, Ibo; Hermann, Julia; Hopster, Jeroen; Lenzi, Dominic; Nyholm, Sven; Taebi, Behnam; Ziliotti, Elena (Open Book Publishers, 2023)
Technologies shape who we are, how we organize our societies and how we relate to nature. For example, social media challenges democracy; artificial intelligence raises the question of what is unique to humans; and the possibility to create artificial wombs may affect notions of motherhood and birth. Some have suggested that we address global warming by engineering the climate, but how does this impact our responsibility to future generations and our relation to nature? This book shows how technologies can be socially and conceptually disruptive and investigates how to come to terms with this disruptive potential. Four technologies are studied: social media, social robots, climate engineering and artificial wombs. The authors highlight the disruptive potential of these technologies, and the new questions this raises. The book also discusses responses to conceptual disruption, like conceptual engineering, the deliberate revision of concepts.